Observations of glitches in PSR 0833-45 and 1641-45 - Flanagan, Claire Susan (Rhodes University, Faculty of Science, Department of Physics and Electronics, 1996)
An eleven-year series of radio timing observations of 0833- 45 (Vela) and PSR 1641- 45 is presented. During this time, five large spin-ups ("glitches") were observed in 0833- 45 and one in 1641-45. The stellar response to these events is investigated, and the three relat ively long complete inter-glitch intervals in 0833-45 are modeled. The results are of relevance to studies of the interiors of neutron stars. The initial aim of the project - to obtain good observational coverage of large glitches in the Vela pulsar - was successfully achieved, and high quality observations of the periods between glitches were obtained as a by-product. The results of the analysis presented here provide support for the existence of both linear and non-linear coupling in the Vela pulsar, and put a limit on the former in PSR 1641- 45. The recently observed existence of a rapidly recovering component of part of a glitch in Vela was verified in the subsequent glitch, although there is now evidence to contradict the suggestion that this component involves a particular region of the star that is implicated in every glitch. Observations of a recent glitch in the same pulsar have resolved a small component of the spin-up; such a component has not been reported for any other large glitch.
Keywords: Pulsars; Neutron stars